Leadership Strategies for Managing Human and Technological Diversity in the Industrial 5.0 Era: A Systematic Review - Manurung, John Sihar; Nugroho, Febriawan Ardi; Sitorus, Sunday Ade; Ardiani, Winda; Aditi, Bunga (Journal of Ecohumanism, 2024)
The problem formulation that arises from this research is how the efforts made by leaders in the industrial era 5.0 overcome problems related to the process of managing HR diversity and technological changes in increasing business innovation in order to increase business productivity and business sustainability, so that they can survive the changes that exist. This research focuses on discussing the efforts of leaders to overcome the problems of the process of managing HR diversity and technological changes in the 5.0 era in order to increase business innovation to increase business productivity and business sustainability. The results of the data analysis used used descriptive qualitative analysis using literature studies through systematic literature review. The research method uses a quantitative descriptive method of data analysis using the structural equation model (SEM) method, where the results of data processing with the SEM method are carried out with the PLS application. From the results of the study, it is concluded that the 5.0 leadership efforts in overcoming the management of HR diversity in increasing business innovation, namely building an inclusive culture, recognizing and appreciating diverse contributions, empowering employees, building intercultural skills, supporting inclusive research and development, using technology that supports engagement and collaboration and diversity-oriented monitoring and evaluation. The results concluded that the 5.0 leadership efforts in overcoming technology management in increasing business innovation, namely a deep understanding of technology, creating an environment that supports technological innovation, focusing on employee engagement and skills, partnering with technology experts, using technology for collaboration and communication, encouraging a culture of experimentation and learning, continuous review of processes and practices and recognition and reward for innovative contributions. Along with managing the diversity of human resources and technology in increasing business innovation, it can create more creativity and make leaders have to follow the direction and be able to adapt to changes so that the company can improve its performance and can continue to run its business optimally and be able to meet consumer needs properly.